Human Milk Fatty Acid Composition Is Associated with Dietary, Genetic, Sociodemographic and Environmental Factors in the CHILD Cohort (P08-114-19). (24th October 2019) - Miliku, Kozeta; Duan, Qing Ling; Moraes, Theo J; Becker, Allan B; Mandhane, Puishkumar; Turvey, Stuart E; Lefebvre, Diana; Takaro, Tim K; Sears, Malcolm; Subbarao, Padmaja; Field, Catherine J; Azad, Meghan B
Abstract: Objectives: Human milk fatty acids impact infant growth and development, and their composition is highly variable. We aimed to characterize milk fatty acid composition in a large pregnancy cohort and identify factors that influence their variability. Methods: Among 1094 mothers from the CHILD cohort, we analyzed milk collected at 3–4 months postpartum. Fatty acids were measured by high-resolution capillary gas-liquid chromatography. Individual fatty acids, total saturated (SFA), monounsaturated (MUFA), n3 and n6-polyunsaturated fatty acids (n3-PUFA and n6-PUFA) were analyzed as standard deviation scores and using principal components analysis (PCA). Maternal diet, sociodemographic, health and environmental factors were self-reported. Single-nucleotide polymorphisms were assessed in genes encoding fatty acid desaturase 1 ( FADS1 rs174556) and FADS2 (rs174575). Results: Using PCA, we identified four milk fatty acid patterns: 'MUFA and low SFA', 'high n6-PUFA', 'high n3-PUFA' and 'high medium-chain fatty acids'. In multivariable-adjusted analyses, fish oil supplementation and fatty cold water fish intake were positively associated with docosohexanoic acid and the "high-n3-PUFA" pattern. Mothers carrying the minor allele of FADS1 rs174556 (C > T) had lower proportions of arachidonic acid (ARA). Independent of dietary and genetic factors, Asian ethnicity was associated with higher linoleic acid and total n3-PUFA. Ethnic differences in ARA were explained by the FADS1 genotype. Maternal obesity was independently associated with higher total SFA and 'high medium-chain fatty acid' pattern, and lower total MUFA. Lactation stage, season, study site, and maternal education were also independently associated with some milk fatty acids. No associations were observed for maternal age, parity, smoking, delivery mode, or infant sex. Conclusions: These results suggest that a combination of diet, genetics, sociodemographic, health and environmental factors influence human milk fatty acid patterns. Together, these factors explained about 25% of the variation observed in n3-PUFAs and n6-PUFAs and about 10% of the variation observed in SFAs and MUFAs. Implications of these findings for maternal and infant health requires further research. Funding Sources: Manitoba Medical Service Foundation; Children's Hospital Research Institute of Manitoba; CIHR; AllerGen.